2021
DOI: 10.1111/jocs.15850
|View full text |Cite
|
Sign up to set email alerts
|

Network meta‐analysis of treatment strategies in patients with coronary artery disease and low left ventricular ejection fraction

Abstract: Objective: The optimal treatment strategy in patients with coronary artery disease (CAD) and low left ventricular ejection fraction (LVEF) remains controversial. Herein, we conducted a network meta-analysis comparing coronary artery bypass graft (CABG), percutaneous coronary intervention (PCI), and optimal medical therapy (OMT) in patients with CAD and low LVEF.Methods: MEDLINE and EMBASE were searched through March, 2021 to identify randomized controlled trials (RCTs) and propensity-score matched (PSM) studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…At three years of follow up, PCI reduced ACM or readmission rates [Brophy 2021]. A network meta-analysis of treatment strategies in patients with CHD and left ventricular dysfunction by Yokoyama et al showed that ACM was similar between CABG and PCI after adjustment for stenting in the PCI group [Yokoyama 2021]. From the above studies, it can be concluded that PCI can be used to treat CHD complicated with HFrEF, and its efficacy may be like that of CABG.…”
Section: Discussionmentioning
confidence: 99%
“…At three years of follow up, PCI reduced ACM or readmission rates [Brophy 2021]. A network meta-analysis of treatment strategies in patients with CHD and left ventricular dysfunction by Yokoyama et al showed that ACM was similar between CABG and PCI after adjustment for stenting in the PCI group [Yokoyama 2021]. From the above studies, it can be concluded that PCI can be used to treat CHD complicated with HFrEF, and its efficacy may be like that of CABG.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ono et al 15 just a few days ago highlight in this extended follow‐up of the SYNTAX trial 16 that there were no significant differences at 10 years in all‐cause death and estimated life expectancy between PCI and CABG in the elderly (>70 years). These latest studies do not specifically address ventricular function as the current meta‐analysis does 11 . In the end, it is all about statistics?…”
mentioning
confidence: 95%
“…These latest studies do not specifically address ventricular function as the current meta-analysis does. 11 In the end, it is all about statistics? Is everybody trying to squeeze data as much as possible aiming at convincing the others by defending a specific hypothesis?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of evaluation of the LV function before PCI may result in the failure to select the optimal revascularization protocol. In a 2021 network meta-analysis by Yujiro Yokoyama et al [9], coronary-artery bypass grafting (CABG) remained the treatment of choice in patients with coronary artery disease and low LV ejection fraction (LVEF). Studies have shown that approximately one-third of patients who undergo PCI [10][11][12] suffered from LV dysfunction-an important predictor of post PCI death and major adverse cardiac events (MACE) [13,14].…”
Section: Introductionmentioning
confidence: 99%